Pendidikan Inklusif di Indonesia: Peluang dan Tantangan - Biantoro, Oktio Frenki; Rahmatullah, Asep (Afkaruna: International Journal of Islamic Studies (AIJIS), 2024)
Inclusive education in Indonesia in recent years has received appreciation from several researchers. Inclusive education itself is actually not something that is "foreign" to the Indonesian people. As a heterogeneous nation, inclusive education is precisely something that "must" exist. The study of inclusive education in Indonesia uses library research (Library Research). This study concludes that one of the opportunities for inclusive education in Indonesia is the presence of a national education system law that supports inclusive education policies. Meanwhile, the main challenge is the readiness of teachers who are not yet able to deal with children with special needs.